An investigation into the early literacy skills of English second language learners in South Africa. Issue 2 (June 2020) - Manten, Aileen; le Roux, Mia; Geertsema, Salomé; Graham, Marien
This study employs the Comprehensive Emergent Literacy Model (CELM) theoretical framework, as it refers to the impact of context on learning early literacy skills. It is relevant to this study as the participants were English second language learners from cultures, communities, and demographics different from those of English first language speakers in South Africa. Early literacy skills, specifically phonological awareness (PA), are predictive of later literacy success. Many English second language (EL2) learners are unable to develop language and early literacy skills. Foundational skills such as general PA skills, often need explicit instruction to prepare the learners to learn to read in English. Twenty-one EL2 Grade 1 learners in an English medium private school in South Africa were selected as participants. Early literacy skills were assessed at the beginning of Grade 1. Reading, spelling, and reading comprehension skills were assessed after two terms in Grade 1 to determine if there is a correlation between early and later literacy skills. Results indicated significantly strong positive correlations between early literacy and later literacy skills. These results and previous research suggest that EL2 learners must be exposed to high-quality early literacy skills as early as possible to provide them with a foundation for future literacy success.